Exorcising the exotic in Joseph Conrad's Malayan works - French, Zenaida B. (Danyag :the UPV journal of humanities and social sciences)
"Joseph Conrad's Malayan works are usually misread as exotic adventure stories about white men, generally Europeans, living in comparative isolation in an alien environment and culture. In these works, the White Man is shown failing in his enterprise of bringing Progress and Civilization to the "barbaric" peoples of the East, putting under a cloud the moral justification for such an enterprise. In a deconstructive reading, Conrad's Malayan works reveal the White Man's burden as a covert act of political subjugation."